The Influence of Science, Technology, Engineering, and Mathematics (STEM) Learning Models to Improve Students' Critical Thinking Skills - Gusman, Tania Avianda; Listanty, Ruri Vhirgiani; Azizah, Dewiantika (Journal of Educational Chemistry (JEC), 2023)
Low learning activity in science students causes a decrease in critical thinking skills. This can be seen from the results of learning redox material under the Kriteria Ketuntasan Minimal (KKM) of 75 in one of the high schools in Cirebon. Therefore, this study aims to improve students' critical thinking skills by using the Science, Technology, Engineering, and Mathematics (STEM) model for redox material in class X IPA MAN 1 Cirebon City. The research method used a Nonequivalent Control Group Design. Sampling was carried out by Purposive sampling consisting of class X IPA 5 as an experimental class and class X IPA 4 as a control class. The instruments used are critical thinking ability tests, observation sheets, and questionnaires. The selection of a sample based on the KKM of a class was revealed from discussions with a chemistry teacher. The development of the T-test obtained a sig value. 0.000 0.05 and an n-gain score of 0.71 with the highest category. The results showed improved critical thinking skills after being given STEM learning. Students respond very well to the teaching that has been done using the STEM model. Based on the results of the t-test and N-gain test, it can be concluded that the Science, Technology, Engineering, and Mathematics (STEM) learning model can improve students' critical thinking skills on redox material.